Sensorimotor and inhibitory control in aging FMR1 premutation carriers - Fielding-Gebhardt, Heather; Kelly, Shannon E.; Unruh, Kathryn E.; Schmitt, Lauren M.; Pulver, Stormi L.; Khemani, Pravin; Mosconi, Matthew W. (Frontiers in Human Neuroscience, 2023)
Aging FMR1 premutation carriers are at risk of developing neurodegenerative disorders, including fragile X-associated tremor/ataxia syndrome (FXTAS), and there is a need to identify biomarkers that can aid in identification and treatment of these disorders. While FXTAS is more common in males than females, females can develop the disease, and some evidence suggests that patterns of impairment may differ across sexes. Few studies include females with symptoms of FXTAS, and as a result, little information is available on key phenotypes for tracking disease risk and progression in female premutation carriers. Our aim was to examine quantitative motor and cognitive traits in aging premutation carriers. We administered oculomotor tests of visually guided/reactive saccades (motor) and antisaccades (cognitive control) in 22 premutation carriers (73% female) and 32 age- and sex-matched healthy controls. Neither reactive saccade latency nor accuracy differed between groups. FMR1 premutation carriers showed increased antisaccade latencies relative to controls, both when considering males and females together and when analyzing females separately. Reduced saccade accuracy and increased antisaccade latency each were associated with more severe clinically rated neuromotor impairments. Findings indicate that together male and female premutation carriers show a reduced ability to rapidly exert volitional control over prepotent responses and that quantitative differences in oculomotor behavior, including control of visually guided and antisaccades, may track with FXTAS – related degeneration in male and female premutation carriers.